2013
DOI: 10.1111/faf.12045
|View full text |Cite
|
Sign up to set email alerts
|

Managing fisheries for human and food security

Abstract: We evaluate the current status of the global marine fisheries using the frameworks of conflict, food security and vulnerability. Existing trends suggest that there is likely to be greater food insecurity and fisheries conflicts due to issues such as: declining fishery resources; a North–South divide in investment; changing consumption patterns; increasing reliance on fishery resources for coastal communities; and inescapable poverty traps creating by low net resource productivity and few alternatives. Conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(135 citation statements)
references
References 99 publications
(214 reference statements)
2
129
0
4
Order By: Relevance
“…Second, Ostrom argues that a self-governed CPR is one wherein 'major appropriators of the resource, are involved over time in making and adapting rules within collectivechoice arenas' and in our modern political economies it is highly usual that 'in a self-governed system, participants make many, but not necessarily all, rules that The Daudkandi model of community floodplain aquaculture in Bangladesh 857 affect the sustainability of the resource system and its use' (Ostrom 2002(Ostrom , 1317. Initially in the co-management era, primary partners in managing a resource were government and the users, and that regime has been looked into through Ostrom's framework (Yandle 2003(Yandle , 2008Gelcich et al 2006;Schreiber and Halliday 2013;McClanahan et al 2015). That clear dichotomy has changed in subsequent years through various experimentations, and in the case of present study, as will be shown, community users formed the main partnership with the NGO without any government initiative framework for and involvement in managing their resource.…”
Section: Introductionmentioning
confidence: 84%
“…Second, Ostrom argues that a self-governed CPR is one wherein 'major appropriators of the resource, are involved over time in making and adapting rules within collectivechoice arenas' and in our modern political economies it is highly usual that 'in a self-governed system, participants make many, but not necessarily all, rules that The Daudkandi model of community floodplain aquaculture in Bangladesh 857 affect the sustainability of the resource system and its use' (Ostrom 2002(Ostrom , 1317. Initially in the co-management era, primary partners in managing a resource were government and the users, and that regime has been looked into through Ostrom's framework (Yandle 2003(Yandle , 2008Gelcich et al 2006;Schreiber and Halliday 2013;McClanahan et al 2015). That clear dichotomy has changed in subsequent years through various experimentations, and in the case of present study, as will be shown, community users formed the main partnership with the NGO without any government initiative framework for and involvement in managing their resource.…”
Section: Introductionmentioning
confidence: 84%
“…Paralelo à pressão realizada pelos movimentos sociais a pesquisa redirecionou seus objetivos, incluindo questões como pobreza (Jentoft & Onyango, 2010, Béné et al, 2016, Prestrelo et al,2016, marginalização (Ratner et al, 2014) e seguridade alimentar (Mcclanahan et al., 2015) aos tradicionais estudos para gestão dos estoques pesqueiros (Beverton & Holt, 1957, Duarte-Neto et al, 2008, Lessa & Santana, 2016. Em 2010 foi realizado, também em Bankok, o 1.º Congresso Mundial de Pesca Artesanal que consolidou a visão interdisciplinar da matéria entre os pesquisadores.…”
Section: Conteúdo Do Documento E Posicionamento Dos Estados Membrounclassified
“…This consumption of fish is above the level of population growth, with 57% of global fish stocks now fully exploited (i.e., at or very close to their maximum sustainable production) and 30% overexploited [110]. To meet demand and to combat the problems of over fishing wild-caught fish stocks there has been a marked increase in global aquaculture (with much occurring in Asia and Sub-Saharan Africa [111][112][113][114][115]), and a recent World Bank report [116] stated that by 2030, aquaculture will provide close to two thirds of global food fish consumption (186 million tons). With the increasing use of aquaculture, Merino et al [117] have determined that the fish demand by 2050 will be met, but only if fish resources are managed sustainably and the animal feeds industry reduces its reliance on wild fish.…”
Section: Reducing Meat and Animal-based Foodsmentioning
confidence: 99%